O discurso publicitário em foco: questões sobre dialogismo e gênero do dicurso - Viccari Neto, Lino [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The subject of this research is the publicity discourse, in its configuration as speech genres, according to theoretical-methodological perspective in Bakhtinian Studies. Considering that there are infinite fields of human communication, Bakhtin says that there is also infinity of speech genres. However, according to the author, every sphere of human activity produces, and even requires, certain genres, with theirs thematic, compositional and stylistics aspects defined according to social-ideological values that materialize in that sphere and in the dialogue in which the texts are produced. The objective of this research is to study, according to this theoretical-methodological perspective, a print advertising piece by the Brazilian Federal Government, conveyed in the Língua Portuguesa magazine, with themes concerning the national public education. We analyze how the image of author is built and how the image of the Other is outlined by that author. It is assumed that the gender to which an advertising piece belongs intends to sell a product or idea. One of the specific objectives of this research is to identify what is being sold in the advertising piece that we analyze and what discursive and stylistic resources are utilized to achieve success in what it intends to promote. The results show that the author (in the voice of the Federal Government), while adopting the position of information-holder, also puts himself in the same plane of the reader, where everyone is responsible for the development of education in the country. The advertising piece intends to project a positive image of the Government, and this project of saying is realized, in the analysis, in the compositional aspects of the text as well in the stylistic aspects

O tema desta pesquisa é o discurso publicitário, em sua configuração como gênero do discurso, segundo perspectiva teórico-metodológica de estudos bakhtinianos. Considerando que são infinitos os campos da comunicação humana, Bakhtin defende que existe uma infinidade de gêneros do discurso. Mas, segundo o autor, cada esfera da atividade humana produz, e até mesmo requer, determinados gêneros, com seus aspectos temático, composicional e estilístico definidos segundo os valores sócio-ideológicos que se materializam nessa esfera e no diálogo que em se produzem os enunciados. O objetivo da pesquisa é estudar, segundo essa perspectiva teórico-metodológica, uma peça publicitária impressa do Governo Federal do Brasil, veiculada na revista Língua Portuguesa e que tem por tema a educação pública nacional. Analisa-se como se constrói nela uma imagem de autor e como se esboça a imagem do outro criada por esse autor. Parte-se do pressuposto de que o gênero ao qual pertence uma peça publicitária tem por função vender um produto ou uma ideia. Um dos objetivos específicos da pesquisa é identificar o que está sendo vendido na peça publicitária que se analisa e quais são os recursos discursivos e estilísticos utilizados para obter êxito nessa função. Os resultados apontam que o autor (na voz do Governo Federal), ao mesmo tempo em que assume uma postura de detentor da informação, também se coloca no mesmo plano do leitor, em que todos são responsáveis pelo desenvolvimento da educação no país. A peça publicitária pretende passar uma imagem positiva do Governo, e esse projeto de dizer se percebe, na análise, tanto nos aspectos composicionais do enunciado quanto nos estilísticos
Keywords: Bakhtin, M. M. (Mikhail Mikhailovich), 1895-1975; Análise do discurso; Autoria; Speech genres; Publicity discourse; Bakhtinian studies; Media; Authorship